Formal Thought Disorder and language impairment in schizophrenia - Marcia Radanovic; Rafael T. de Sousa; L. Valiengo; Wagner Farid Gattaz; Orestes Vicente Forlenza (Arquivos de Neuro-Psiquiatria)
Schizophrenia is a psychiatric illness in which disorders of thought content are a prominent feature. The disruption of normal flow of thought, or “Formal Thought Disorder” (FTD), has been traditionally assessed through the content and form of patients’ speech, and speech abnormalities in schizophrenia were considered as a by-product of the disruption in conceptual structures and associative processes related to psychosis. This view has been changed due to increasing evidence that language per se is impaired in schizophrenia, especially its semantic, discursive, and pragmatic aspects. Schizophrenia is currently considered by some authors as a “language related human specific disease” or “logopathy”, and the neuroanatomical and genetic correlates of the language impairment in these patients are under investigation. Such efforts may lead to a better understanding about the pathophysiology of this devastating mental disease. We present some current concepts related to FTD as opposed to primary neurolinguistic abnormalities in schizophrenia.